AN ANALYSIS OF STUDENTS’ SUPRASEGMENTAL ERRORS IN READING SENTENCES AT SMA NEGERI 4 JENEPONTO - Rindiani; Nurdevi Bte Abdul; Andi asri jumiati (Journal of Language Testing and Assessment, 2022)
This study aims to identify the errors students in intonation and in stressing the word in sentences. This is descriptive qualitative research. Student audio transcripts and an Oxford dictionary were used to process the data. Participants in this study were students of SMAN 4 Jeneponto X IPA 2 semester 2, totaling 15 people who were selected by random sampling technique. A pronunciation test or oral test was used as the primary research instrument, with recordings as a secondary instrument.The results showed that there were 2 errors in intonation made by students of class X IPA 2 semester 2 SMAN 4 Jeneponto, namely rising intonation and falling intonation errors. Then there is an error in stressing the word in the sentence, which lies in the verbs and adjectives. It can be concluded that the errors made by students are caused by a lack of knowledge and awareness of students in terms of pronunciation, especially suprasegmental sounds.